Comparison of TOR lubrication systems on the iron ore line - Asplund, Matthias; Nordmark, Thomas; Gustafsson, Per (Luleå tekniska universitet, Drift, underhåll och akustik, 2015)
The Iron Ore Line (IOL) is a 473 km long track section which is located in northern Sweden and northern Norway, and has been in operation since 1903. The northern part is located above the Arctic Circle. The IOL is mainly used to transport iron ore and pellets from the mines in Kiruna and Malmberget to Narvik Harbour (Norway) in the northwest and Luleå Harbour (Sweden) in the southeast. The track section on the Swedish side is owned by the Swedish Government and managed by Trafikverket (the Swedish Transport Administration), while the ore wagons are owned and managed by the freight operator (LKAB).The IOL has seen a considerable increase in the axle load and traffic volume recently. Due to the introduction of new vehicles with a 30-ton axle load, the rails were gradually replaced between 2006 and 2009 with heavier rails, generally with a steel grade of 350LHT. The rail and wheels suffer from rolling contact fatigue (RCF) due to high friction between the rail and wheel. To control the wheel-rail interface, wayside top-of-rail (TOR) lubrication can be used. The reliability of the TOR lubrication equipment and the lubricants in northern conditions has not been investigated, and the long-term maintenance support required for TOR lubrication is unknown to the infrastructure manager. Furthermore, can TOR lubrication reduce the rail and wheel maintenance costs? This project has been conducted through collaboration between the main operator (LKAB) and the infrastructure manager (Trafikverket); the costs have been shared and the results analysed in collaboration. This paper describes the test period of two years, using two different TOR lubrication systems in two different places on the IOL, one situated in the northern loop and one in the southern loop, each with different operational conditions. The paper shows the actual operational conditions for the pilot test locations, the friction value close to the systems, the rail forces during the test period and some results for the noise measurements. Furthermore, the paper ...